From group-based learning to individual educational trajectories in online platforms - Yuriy Mlavets; Kateryna Moskvychova; Olena Tymoshenko (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. Ensuring access to adaptive distance mathematics courses has never been more critical. The disruptions caused by the COVID-19 pandemic and ongoing war in Ukraine have significantly impacted education, exposing gaps in students’ mathematical preparation. This is particularly concerning for students pursuing technical, economic, and IT disciplines, where a strong foundation in mathematics is essential. Despite the growing need for high-quality remote learning resources, the open-access mathematics courses currently available in Ukraine fail to comprehensively cover problematic topics, leaving students underprepared for universitylevel studies. Standard vs. Innovative Educational Approaches. A useful way to conceptualize the differences between traditional and modern mathematics education is through a comparative framework: Several online platforms offer mathematics courses, but they do not fully address the specific needs of Ukrainian students. Coursera – Provides a variety of mathematics courses from international universities, but many of them require payment for certification and lack customization for the Ukrainian curriculum. Khan Academy – Offers a broad selection of math topics, but its structure does not always align with the depth required for technical and economic specializations.
Keywords: online learning; group-based learning; online platform